2003
DOI: 10.1063/1.1570514
|View full text |Cite
|
Sign up to set email alerts
|

Surface nanostructuring of borosilicate glass by femtosecond nJ energy pulses

Abstract: We report on a feature, that of hillock-shaped damage, formed on a glass surface by femtosecond pulses of t p ϭ180 fs ͓full width at half maximum ͑FWHM͒ value͔ duration produced by a recording beam focus with energy of 5 nJ/pulse at 800 nm wavelength ͑the corresponding irradiance of about 7.6 TW/cm 2 was evaluated for a 0.68 m FWHM spot size͒. Single hillocks of 40-50 nm height were recorded reproducibly in single-pulse irradiation. Surface nanopatterning over a large, curved area ͑over 200 m 2 ) can be achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…To explore the role of Coulomb explosion for nanostructuring of material surfaces is the subject of considerable interest. Some good examples in which surface modification of different materials by femtosecond laser irradiation is explained on the basis of CE are: the hillock-shaped damage, formed on a glass surface by femtosecond pulses of 180 fs with energy of 5 nJ/pulse at 800 nm wavelength is reported by Vanagas et al [20]. The lateral crosssection of the hillocks observed was 115-155 nm with a height of 40-70 nm.…”
Section: Introductionmentioning
confidence: 92%
“…To explore the role of Coulomb explosion for nanostructuring of material surfaces is the subject of considerable interest. Some good examples in which surface modification of different materials by femtosecond laser irradiation is explained on the basis of CE are: the hillock-shaped damage, formed on a glass surface by femtosecond pulses of 180 fs with energy of 5 nJ/pulse at 800 nm wavelength is reported by Vanagas et al [20]. The lateral crosssection of the hillocks observed was 115-155 nm with a height of 40-70 nm.…”
Section: Introductionmentioning
confidence: 92%
“…Surface bulging and ablation of a borosilicate glass (cover glass) under high repetition rate irradiation by fs-laser pulses takes place via interplay of strongly localized energy absorption, low heat conductance, ablation, and surface tension effects even at low pulse energy as used in this study. 24 Here, it was found that such structural modification of glass surface was required to obtain water insoluble crystalline silk. Since silk conformational transformation has a chemical origin, e.g., radiolysis of water and free radicals generation, establishing of crosslinks, and a thermal activation has only secondary effect, a possible explanation can be found in the onset of ablation at which silk printing occurred.…”
Section: -3mentioning
confidence: 99%
“…The point-spread function (PSF) shown in Figure 5 is presented in normalized optical coordinates and the actual r, z dimensions of the focus can be found for the specific R, F values (the numerical aperture is NA ¼ n sinðÞ ' nR=F, here n is the refractive index). More precise estimations of the focal spot size would require accounting for the spatial profile of the laser beam, its clipping by the aperture of the objective lens, 44 vectorial nature of electromagnetic radiation 20,40 and spatio-temporal distortions of the laser radiation. 45,46 These factors typically reduce the resolution of DLW process.…”
Section: Beam Delivery and Spatio-temporal Distortionsmentioning
confidence: 99%